(untitled) (AYUSHDHARA, 2020)
Eye is a highly specialized sense organ serving the most important function of vision. Vision is the most vital of all the senses. Almost 90% of knowledge is perceived only through eyes. Humans are mostly dependent upon the vision for their day to day work. Hence any hindrance to this means a major handicap. Ayurveda advises that all sincere efforts should be made to protect the eyes as long as one is alive. Ayurvedic classical texts have mentioned about eye and its diseases since Vedic and Samhita kala, thus showing the importance of eye and ways to protect it. In Ayurveda, clinical features related to visual disturbances are generally seen in Dristigata roga. The anatomical consideration of the Patala and symptoms of the vitiated Dosa situated in these Patala reveals that the word Timira which is described as an ocular pathology in Ayurveda, is nothing but error of refraction. The part of clinical features of Timira (Pratham Patalagata Timira) can be correlated to myopia. Myopia is a common refractive condition that can affect the clarity of vision, limit occupational choices, and contribute to increased risk for vision threatening conditions. Myopia commonly known as short-sightedness is the most common ocular disease in the world which substantially graves the social, economic and educational life. It is a type of refractive error in which parallel rays of light coming from infinity are focused in front of the retina, when accommodation is at rest. Poor distant vision is one of the main symptoms of myopia. Thus, on the basis of symptoms of Timir roga and simple myopia a correlation can be established between the two diseases.